Haematological malignancies in sub-Saharan Africa: east Africa as an example for improving care. Issue 10 (October 2021) - Okello, Clement D; Niyonzima, Nixon; Ferraresso, Marta; Kadhumbula, Sylivestor; Ddungu, Henry; Tarlock, Katherine; Balagadde-Kambugu, Joyce; Omoding, Abrahams; Ngendahayo, Louis; Karagu, Alfred; Mwaiselage, Julius; Harlan, John M; et al.
Summary: Haematological malignancies account for almost 10% of all cancers diagnosed in sub-Saharan Africa, although the exact incidences and treatment outcomes are difficult to discern because population-based cancer registries in the region are still underdeveloped. More research on haematological malignancies in sub-Saharan Africa is required to establish whether these cancers have a natural history similar to those diagnosed in high-income countries, about which more is known. Several factors negatively affect the outcome of haematological malignancies in sub-Saharan Africa, showcasing a need for improved understanding of the clinicobiological profile of these cancers to facilitate prevention, early detection, diagnosis, and appropriate treatment through increased capacity building, infrastructure, community awareness, coordinated resource mobilisation, and collaboration across the world. The east African governments have pooled resources for common investments to tackle non-communicable diseases, developing the East Africa's Centres of Excellence for Skills and Tertiary Education project funded by the African Development Bank, an initiative that could be replicated for the care of haematological malignancies in other countries in sub-Saharan Africa. Translation: For the French translation of the abstract see Supplementary Materials section.